LoopSOM: A Robust SOM Variant Using Self-Organizing Temporal Feedback Connections - Pinto, Rafael C.; Engel, Paulo M. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2009)
This paper introduces feedback connections into a previously proposed model of the simple and complex neurons of the neocortex. The original model considers only feedforward connections between a SOM (Self-Organizing Map) and a RSOM (Recurrent SOM). A variant of the SOM-RSOM pair is proposed, called LoopSOM. The RSOM sends predictions to the SOM, providing more robust pattern classification/recognition and solving ambiguities.